Ground-based infrastructure for monitoring and characterizing intermediate-scale ionospheric irregularities at mid-latitudes - Mrak, Sebastijan; Coster, Anthea J.; Groves, Keith; Nikoukar, Romina (Frontiers in Astronomy and Space Sciences, 2023)
We discuss potential science investigations at mid-latitudes enabled by a modern, space-weather-grade, ground-based Radio-Frequency network of scintillation receivers which encompasses Global Navigation Satellite Systems and Beacon receivers, along with coherent radars, and leveraging radio astronomy infrastructure for space weather application. The primary scientific research addresses the controlling space weather drivers for the structuring of mid-latitude ionospheric plasma at intermediate scales (10s of meters—10s of kilometers), their relationship with larger density structures, and their impacts on the trans-ionospheric radio links. These irregularities scintillate the signals impairing the radio link integrity and the underpinning services. The suggested science investigations are currently unable to be fully accomplished because of missing high-fidelity and long-term observations at satisfactory spatial coverage. We discuss the physics responsible for the radio wave disturbances and their impacts, review the current state of knowledge based on available observations, and outline a plan for developing the necessary infrastructure by leveraging existing ground-based distributed observatories that will enable novel scientific investigations and will be synergistic with other geoscience divisions such as seismology, geology, and meteorology.